An ultra scale‐down methodology to characterize aspects of the response of human cells to processing by membrane separation operations. Issue 6 (23rd February 2017) - Masri, Maria Fernanda; Lawrence, Kate; Wall, Ivan; Hoare, Michael
ABSTRACT: Tools that allow cost‐effective screening of the susceptibility of cell lines to operating conditions which may apply during full scale processing are central to the rapid development of robust processes for cell‐based therapies. In this paper, an ultra scale‐down (USD) device has been developed for the characterization of the response of a human cell line to membrane‐based processing, using just a small quantity of cells that is often all that is available at the early discovery stage. The cell line used to develop the measurements was a clinically relevant human fibroblast cell line. The impact was evaluated by cell damage on completion of membrane processing as assessed by trypan blue exclusion and release of intracellular lactate dehydrogenase (LDH). Similar insight was gained from both methods and this allowed the extension of the use of the LDH measurements to examine cell damage as it occurs during processing by a combination of LDH appearance in the permeate and mass balancing of the overall operation. Transmission of LDH was investigated with time of operation and for the two disc speeds investigated (6, 000 and 10, 000 rpm or ϵ max  ≈ 1.9 and 13.5 W mL −1, respectively). As expected, increased energy dissipation rate led to increased transmission as well as significant increases in rate and extent of cell damage. The method developed can be used to test the impact of varying operating conditions and cell lines on cell damage and morphological changes. Biotechnol. Bioeng. 2017;114: 1241–1251. © 2017 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : The paper from Masri et al. describes the use of an ultra scale‐down (USD) device for aspects of the characterization of the response of a human cell line to membrane‐based processing. Using a small quantity of cells, this paper evaluates the impact on cell damage as assessed by trypan blue exclusion and release of intracellular lactate dehydrogenase (LDH). The method developed can be used to test the impact of varying operating conditions and cell lines on cell damage and morphological changes.